A novel fuzzy integral sliding mode current control strategy for maximizing wind power extraction and eliminating voltage harmonics. (1st June 2015) - Yin, Xiu-xing; Lin, Yong-gang; Li, Wei; Gu, Ya-jing; Liu, Hong-wei; Lei, Peng-fei
Abstract: A novel fuzzy integral sliding mode current control strategy is proposed to extract the maximum wind power and eliminate the high-order voltage harmonics at the generator side for a direct-driven wind energy system. In this control strategy, a fuzzy logic generator is employed to derive the peak power points based on the variations of measured DC-side voltage and current. An integral sliding mode current controller is then designed in this control strategy to track the peak power points. A harmonic compensator is also built inside the fuzzy logic generator for minimizing the voltage harmonics. Major issues in the design and implementation of the control strategy such as detailed design procedure and stability condition have been presented. Comparative experimental results have demonstrated the achievable significant improvements on the maximum power extraction and harmonic elimination by using the proposed control strategy as compared with a conventional control method. Highlights: A novel fuzzy integral sliding mode current control strategy is proposed for wind energy system. The control strategy is designed based on fuzzy reasoning and direct current control. The control strategy can extract the maximum wind power with high efficiency. The control strategy can eliminate the generator side voltage harmonics with good accuracy.